Capacity Building in Cyberspace as an Instrument of Foreign Policy. Issue 1 (February 2016) - Pawlak, Patryk
Abstract: The positive impact of the Internet on human development depends on security and safety of the digital environment. With the share of developing countries in the global Internet population increasing rapidly, addressing the threats posed by malicious cyber activities is a clear priority. The purpose of this article is to explore the linkages between international debates on cyber‐related issues (i.e. Internet governance, cybercrime, cybersecurity, or international norms) and cyber capacity building. Specifically, the article analyses capacity building projects by the Council of Europe and International Telecommunication Union to answer if and how they can be used as a tool in foreign policy. This question stems from the assumption that capacity building as a process focused on human resources development, organisational arrangements and legal and institutional frameworks is ultimately aimed at deep societal and political transformation. Abstract : There is no single 'good' model for securing cyberspace – therefore, the exchange of good practices between individual countries and regional organisations may help streamline ongoing efforts.